Switzerland : Detailed Assessment of Implementation-IOSCO Objectives and Principles of Securities Regulation. (IMF Staff Country Reports; Country Report ;, 2014)
This Detailed Assessment of Implementation on the International Organization of Securities Commissions (IOSCO) Objectives and Principles of Securities Regulation discusses that Switzerland has made progress in addressing the recommendations from the IOSCO assessment of the 2001-2002 Financial Sector Assessment Program. In supervision, the Swiss Financial Market Supervisory Authority (FINMA) has further developed the risk-based supervisory system that it uses to determine the supervisory approach for each supervised entity. FINMA's enforcement powers have recently been enhanced through the introduction of specific prohibitions on insider trading and market manipulation in the Federal Act on Stock Exchanges and Securities Trading. The Swiss authorities will face a significant challenge in coping with the upcoming securities regulatory overhaul. The planned framework will impact on practically all the areas of FINMA, as it is likely to require the assumption of new tasks in relation to the regulation and supervision of the issuance of unlisted securities, financial market infrastructures, independent asset managers, and conduct of business of banks and securities dealers.